Regulation of Adipogenesis Through Differential Modulation of ROS and Kinase Signaling Pathways by 3, 4′‐Dihydroxyflavone Treatment. Issue 5 (6th January 2017) - Han, Jihae; Choi, Hye Yeon; Dayem, Ahmed Abdal; Kim, Kyeongseok; Yang, Gwangmo; Won, Jihye; Do, Sun Hee; Kim, Jin‐Hoi; Jeong, Kyu‐Shik; Cho, Ssang‐Goo
ABSTRACT: Studies on adipogenesis may be important for regulating human and/or animal obesity, which causes several complications such as, type II diabetes, hypertension, and cardiovascular disease, thus giving rise to increased economic burden in many countries. Previous reports revealed that various flavonoids have anti‐apoptotic, antioxidant, and cell differentiation‐regulating activities with a number of physiological benefits, including protection from cardiovascular disease, cancers, and oxidative stress. As we found that the hydroxylation patterns of the flavonoid B ring are known to play a critical role in their function, we screened several flavonoids containing different numbers and positions of OH substitutions in B ring for their modulatory property on adipogenesis. In this study, we revealed the anti‐adipogenic activity of the naturally derived flavonoid, 3, 4′‐dihydroxyflavone (3, 4′‐DHF) in murine 3T3‐L1 pre‐adipocytes and equine adipose‐derived stromal cells (eADSCs). We found that treatment with 3, 4′‐dihydroxyflavone (3, 4′‐DHF) led to decreased expression of adipogenic markers and lipid deposition with differential modulation of ROS and kinase signaling pathways. Regulation of ROS generation through the differential modulation of ROS‐regulating gene expression was revealed to have an important role in the suppression of adipogenesis and increase of osteogenesis in eADSCs following 3, 4′‐DHF treatment. These results suggest that the flavonoid 3, 4′‐DHF can be used to regulate adipogenesis in ADSCs, which has potential therapeutic application in regenerative medicine or health care for humans and many sport or companion animals. J. Cell. Biochem. 118: 1065–1077, 2017. © 2016 Wiley Periodicals, Inc. Abstract : Treatment of the naturally derived flavonoid, 3, 4′‐dihydroxyflavone (3, 4′‐DHF) suppressed adipogenesis in murine 3T3‐L1 pre‐adipocytes and equine adipose‐derived stromal cells (eADSCs) through differential modulation of ROS and kinase signaling pathways. These results suggest that the flavonoid can be used to regulate adipogenesis in ADSCs, which has potential therapeutic application in regenerative medicine or health care for humans and many sport or companion animals.